The relationship between love for humanity and economic jihad - Syaidatun Nazirah Abu Zahrin,; Radin Anis Adlina Radin Hasbani,; Mohamad Sabri Haron, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The love for humanity calls for all levels of society to be proactive entities in contributing to global peace and prosperity. Among the values embodied in the love for humanity are volunteerism and philanthropy. The deprivation of a love for humanity makes humans come into conflict with each other and often hurt one another and even to the point of killing and waging wars. This article is based on the questionnaire that surveyed the issue of “Economic Jihad Among Malaysian” and distributed to 500 respondents. This understanding should be disseminated nurtured by working on positive values from the point of Islam and the West. The data was analyzed and compiled based on SPSS analysis. The findings of this study reveal a positive relationship between love for humanity (philanthropy and volunteerism) and economic jihad. This study emphasized the economic jihad, volunteerism and philanthropy as a way of life and daily practice. It suggests that further research should be conducted in the area of humanitarian, Islamic economic and philanthropy.